2000
DOI: 10.1034/j.1399-0004.2000.580510.x
|View full text |Cite
|
Sign up to set email alerts
|

Kyphomelic dysplasia: a rare form of semilethal skeletal dysplasia

Abstract: Kyphomelic dysplasia is a rare form of generalized skeletal dysplasia with about 15 cases described so far in the literature. We present the clinical, radiological, and pathological findings of an antenatally detected female fetus affected with this disorder. The differential diagnoses of prenatal and perinatal semilethal skeletal dysplasias and salient features of documented cases of kyphomelic dysplasia are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Also unlikely are unique syndromes (e.g., Conway, 1958; Bain and Barret, 1959; Dunn and Aponte, 1962; Rath and Thalhammer, 1967; Stüve and Wiedman, 1971; Mahloudji et al, 1974; Eliachar et al, 1975; Stevenson, 1982; Maclean et al, 1983; Burton et al, 1986), in which shortening and bowing of the femora are associated with other deformities. Recent attempts to better delineate some of those conditions (Prasad et al, 2000; Spranger et al, 2000) reemphasized the symptomatic nature of a variety of cases exhibiting bowing of the long bones. Many of those cases were grouped under the general title of “congenital bowing of long bones” (CBLB), meant as nonspecific manifestations of a great number of conditions (Kozlowsky et al, 1978; Hall and Spranger, 1980).…”
Section: Differential Diagnosismentioning
confidence: 99%
“…Also unlikely are unique syndromes (e.g., Conway, 1958; Bain and Barret, 1959; Dunn and Aponte, 1962; Rath and Thalhammer, 1967; Stüve and Wiedman, 1971; Mahloudji et al, 1974; Eliachar et al, 1975; Stevenson, 1982; Maclean et al, 1983; Burton et al, 1986), in which shortening and bowing of the femora are associated with other deformities. Recent attempts to better delineate some of those conditions (Prasad et al, 2000; Spranger et al, 2000) reemphasized the symptomatic nature of a variety of cases exhibiting bowing of the long bones. Many of those cases were grouped under the general title of “congenital bowing of long bones” (CBLB), meant as nonspecific manifestations of a great number of conditions (Kozlowsky et al, 1978; Hall and Spranger, 1980).…”
Section: Differential Diagnosismentioning
confidence: 99%
“…KD is quite similar to other forms of MCD in that it exhibits combined immune deficiency and aplastic anemia. Femoral bowing is a hallmark of KD [23]. Novel mutations were found in the RMRP gene of a patient with KD, including an insertion of T at 194_195 (paternal allele) and a 63C→ T point mutation on the maternal allele.…”
Section: Mdwh (Omim #250460) Is a Disorder In Which Thementioning
confidence: 99%
“…Although it is difficult to infer solid prognostic factors from small numbers, we observed that severe early involvement of long bones (Cases 1 and 2) and early onset of severe oligohydramnios (Case 8) could suggest poor outcome in SWS. Despite the occasional lethal neonatal problems, kyphomelic dysplasia, FH‐UFS and diastrophic dysplasia are compatible with a probably normal life expectancy29–32. The prognosis of Cumming and Antley–Bixler syndromes will depend on the associated anomalies33, 34.…”
Section: Discussionmentioning
confidence: 99%